Sustainability and the UK’s Leading Clothing Retailers - Peter Jones (Athens Journal of Business & Economics)
The UK’s clothing retailers have a global reach which embraces a range of elements including, the production of the raw materials, a variety of treatment and manufacturing processes, retailing, and consumption, and all these elements face a variety of environmental and social challenges, which are increasingly in the public eye. With this in mind, this paper offers an exploratory study into how the UK’s leading clothing retailers are publicly addressing sustainability. The paper reveals that the leading clothing retailers addressed a wide range of issues including strategic corporate commitment; climate change and greenhouse gas emissions; environmental protection; the circular economy; protecting workers in supply chains; diversity, equity and inclusion; health and safety; and links with communities and charitable donations. More generally, the author offered three sets of wider reflections, focused on the different meanings of sustainability and the relative importance of business drivers vis-à-vis environmental and social sustainability drivers; the aspirational and expectational nature of many of the selected companies’ approaches to sustainability; and tensions between sustainability and economic growth.